Competence of an ICT Teacher Concerning Didactic and Methodological Support in Teaching ICT at Primary School - Loudova, Irena (Learning Technologies and Systems, 2021)
The widely accepted rhetoric is that our industrial society has been changing to an information society that manages huge amounts of information, which can be disclosed and processed with the help of information and communication technology (ICT). This fact has been reflected in the revised school curricula, and subsequently in the growing role and importance of both, ICT implementation into non-informatics subjects, and the computer science teachers in schools of all levels. These teachers should master the new competencies related to the changes brought by the Educational Policy 2030 + in the Czech Republic, which clearly defines the implementation of computer science in non-informatics subjects. Our research aimed to find out, through a field survey, the real situation in the field of professional readiness of ICT teachers in selected primary schools - with special regard to the perception of the situation by professional teachers. The results of our survey showed that especially computer science teachers in primary schools are not sufficiently professionally or technically prepared for the implementation of ICT in the teaching of non-informatics subjects. They also encounter several problems that prevent them from successfully applying the new educational strategy. Our findings are important in terms of current developments when the COVID-19 pandemic completely paralyzed full-time teaching and underlined the importance of the educational environment to be prepared for such exceptional situations while accelerating the implementation of computer science in non-informatics subjects.